A a B b C c D d E e F f G g H h I i J j K k L l M m N n O o P p Q q R r S s T t U u V v W w X x Y y Z z 1 2 3 4 5 6 7 8 9 0
Answer:
2.56
Step-by-step explanation:
Answer:
the solution is (-6, 6)
Step-by-step explanation:
This system, y= -1/2x +3 y= -1/3x +4, can be quickly solved for x by letting y = y:
y= -1/2x +3 = y= -1/3x +4. Then -1/2x + 3 = -1/3x +4. The fractional coefficients should be enclosed inside parentheses:
(-1/2)x + 3 = (-1/3)x +4
Let's remove the fractional coefficients. The LCD is (2)(3) = 6. Multiply all four terms by 6, obtaining:
-3x + 18 = -2x + 24
Combining like terms, we get -6 = x.
Find y: substitute -6 for x in either of the given equations:
y= (-1/2)(-6) +3 = 3 + 3 = 6. So y = 6 when x = -6, and the solution is (-6, 6).
Answer:
How to reflect a triangle around the line y=x
Step-by-step explanation:
The rate of change would be D. 4